Rilievo laser scanning a lunga distanza su frana mediante ILRIS LR - Pesci, Arianna; Casula, Giuseppe; Bonali, Elena; Boschi, Enzo (GEOmedia, 2012)
I sistemi laser a scansione terrestre caratterizzati da una lunga portata, cioè capaci di rilevare su distanze fino a 3 km, sono oggi sempre più utilizzati nel monitoraggio del territorio e nel controllo del dissesto o, in generale, delle variazioni morfologiche. Laser scanning survey of landslides by means of long distance ILRIS LR Terrestrial laser scanning (TLS) is a remote sensing technique for high density acquisition of the physical surface of scanned, currently used in geologic surveys, engineering practice, cultural heritage, and mobile mapping. The very long range scanners, allow the acquisition from distances of the order of about 1 km with material characterized by medium/high reflecting properties. At present, the efforts in technological advancements are highly aimed at the extension of maximum range, at the reduction of acquisition time, and so on. The ILRIS LR laser scanner, provided by Optech, is used to survey a very dense populated landslide area in the Tuscany Apennines, in the frame of a scientific experiment planned by INGV to test its performances.